2019
DOI: 10.1186/s12887-019-1701-6
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between mothers’, fathers’, and children’s’ ratings on health-related quality of life in children born with esophageal atresia – a German cross-sectional study

Abstract: Background Esophageal atresia (EA) is a rare congenital malformation, which is characterized by the discontinuity of the esophagus. We investigated the agreement between mothers’, fathers’, and children’s’ ratings on health-related quality of life (HRQOL) in children born with EA. We aimed to broaden the understanding of subjective experiences of HRQOL from different perspectives. We hypothesized that the agreement between mother and father ratings would be high, whereas the agreement between c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 66 publications
2
32
0
Order By: Relevance
“…described HRQoL among children and adolescents born with EA, [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] three of which 32,34,38 also reported on HRQoL among adults (patients >18 years old). The remaining two articles described HRQoL among adults with EA only.…”
Section: Current Literature Regarding Hrqol In Patients Following Ea mentioning
confidence: 99%
See 2 more Smart Citations
“…described HRQoL among children and adolescents born with EA, [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] three of which 32,34,38 also reported on HRQoL among adults (patients >18 years old). The remaining two articles described HRQoL among adults with EA only.…”
Section: Current Literature Regarding Hrqol In Patients Following Ea mentioning
confidence: 99%
“…Small sample sizes motivate investigators to mix children's and parents' HRQoL scores/ratings, 25 which is not appropriate from the methodological perspective, as the views of EA children should be regarded as a primary source of their HRQoL. 37 Several studies are single-center studies, lacking matched controls, and raw data from general samples, which impede the statistical investigations of HRQoL in patients with EA. Some studies also suffer from a large proportion of patients who were lost to follow-up or have low response rates to the HRQoL questionnaires (►Table 1).…”
Section: Strengths and Limitations In Hrqol Assessment Of Patients Afmentioning
confidence: 99%
See 1 more Smart Citation
“…Some centres have also included diagnostic and interventional radiologists and an intensivist 156 . Special emphasis is given to have regular evaluation and follow-up by psychologists because of growing concern about the long-term effect of EA-TEF on the quality of life of the patients and their families [157][158][159][160] .…”
Section: Health Maintenance and Preventionmentioning
confidence: 99%
“…The authors further concluded that congruence in HRQOL assessment of children with rare chronic diseases is important for the long-term well-being of families since discrepancies might have clinical implications regarding the focus of the treatment. 45 Furthermore, since often only one parent is present in pediatric settings, knowing about possible discrepancies in HRQOL ratings between mothers and fathers is important to interpret HRQOL rankings correctly.…”
Section: Challenges In Health-related Quality Of Life Assessment In Tmentioning
confidence: 99%